2022
DOI: 10.3390/ijms232012596
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes and Regulatory Competitive Endogenous RNA (ceRNA) Networks Underlying Intramuscular Fat Content in Yorkshire Pigs with Extreme Fat Deposition Phenotypes

Abstract: Intramuscular fat (IMF) content is vital for pork quality, serving an important role in economic performance in pig industry. Non-coding RNAs, with mRNAs, are involved in IMF deposition; however, their functions and regulatory mechanisms in porcine IMF remain elusive. This study assessed the whole transcriptome expression profiles of the Longissimus dorsi muscle of pigs with high (H) and low (L) IMF content to identify genes implicated in porcine IMF adipogenesis and their regulatory functions. Hundreds of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…In the present study, lowering the dietary SID Lys:NE ratio did not show adverse effects on dressing percentage, average fat thickness, or LEA. The marbling score, which has been proven to directly reflect IMF content [ 17 ], increased in the LR group. The finding offered compelling evidence supporting the notion that a reduction in the dietary SID Lys:NE ratio facilitated IMF deposition, as indicated by the increase in serum TG concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, lowering the dietary SID Lys:NE ratio did not show adverse effects on dressing percentage, average fat thickness, or LEA. The marbling score, which has been proven to directly reflect IMF content [ 17 ], increased in the LR group. The finding offered compelling evidence supporting the notion that a reduction in the dietary SID Lys:NE ratio facilitated IMF deposition, as indicated by the increase in serum TG concentration.…”
Section: Discussionmentioning
confidence: 99%
“…miR-196a is a key regulator of fat deposition [ 89 , 90 ], and our data showed that miR-196a is up-regulated in the adipose tissue of high-FE pigs, in contrast to that of low-FE pigs. In pigs, miR-196a has been reported to be associated with preadipocyte differentiation and adipogenesis [ 91 , 92 ]. Overexpression of miR-196a can increase lipid accumulation and promote preadipocyte differentiation [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared the genetic profiles of Laiwu pigs with different IMF levels, and the results indicated that the different IMF levels between individual pigs may be due to DE lncRNAs and mRNAs associated with lipid droplets and fat deposition [11]. By comparing the whole transcriptome expression profiles of the longest dorsal muscles of pigs with high and low IMF contents in Yorkshire pigs, the results have shown that IMF fat formation in Yorkshire pigs is regulated by the ceRNA network formed by functional lncRNAs and circRNAs [12]. The Ningxiang pig is one of China's most outstanding native pig breeds, renowned for its high and evenly distributed intermuscular fat content, tender meat, and slender muscle fibers [13].…”
Section: Introductionmentioning
confidence: 97%